Composite gas-sensitive material as well as preparation method and application thereof

By introducing the SNO2/In2O3/C composite gas -sensitive material prepared in the organic framework of the tin fundamental element to solve the problem of poor response in the detection of existing oxygenic ingrains in the detection of ethanol, and indirectly judged cooling by detecting the leakage of ethanol indirectly to cool down the cooling of the leakage of ethanol The leakage of the liquid is achieved, which achieves a fast response and safe and stable leak detection effect.

CN119350637APending Publication Date: 2025-01-24GUODIAN NANJING ELECTRIC POWER TEST RES CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411300638.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing tin oxide gas-sensitive materials are poorly responsive in ethanol detection applications, and leakage of cooling media in electrochemical energy storage liquid cooling systems is difficult to detect.

Method used

A composite gas-sensitive material is prepared by introducing indium element into a tin-based metal-organic framework, using a tin-indium-based organic metal framework as a precursor, and forming a SnO2/In2O3/C composite material through a heating reaction, which can be used to detect ethanol and indirectly judge Coolant leaks.

Benefits of technology

The composite gas -sensitive material has a high sensitivity to ethanol, fast and safe and stable in response. It is suitable for the detection technology of electrochemical energy storage cold system, which significantly improves the safety and stability of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350637A_ABST
    Figure CN119350637A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, and discloses a composite gas-sensitive material and a preparation method and application thereof.The method comprises the following steps that 1, in the presence of an organic alcohol solvent, tin salt, indium salt and a carbon source are mixed to react, a product obtained after the reaction is cooled, washed and dried, and a tin-indium-based organic metal framework precursor is obtained; and (2) heating the tin-indium-based organic metal framework precursor for reaction. According to the method for preparing the composite gas-sensitive material, an indium element is introduced into a tin-based metal organic framework, a tin-indium-based organic metal framework with a microsphere structure is adopted as a precursor, the composite gas-sensitive material which also has a microsphere structure and contains SnO2 / In2O3 / C can be prepared, and the composite gas-sensitive material is high in sensitivity to ethanol, high in sensitivity and high in sensitivity to ethanol. The composite gas-sensitive material has the advantages of quick response, safety, stability and the like when being used for detecting ethylene glycol-based cooling liquid mixed with ethanol, and can be widely applied to a liquid leakage detection technology of an electrochemical energy storage liquid cooling system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials, and in particular to a composite gas-sensitive material and a preparation method and application thereof. Background Art

[0002] With the rapid development of society, electrochemical sensing technology has been widely used in industry. Among them, tin oxide, as an important gas-sensitive material, shows high application value in ethanol detection. However, studies have shown that single tin oxide materials have disadvantages such as slow response, lack of response selectivity and high operating temperature during use. Therefore, a new technical solution is urgently needed in the existing technology to solve this problem. By preparing composite gas-sensitive materials, utilizing the synergistic and complementary effects between multiple components, and regulating the structure of the composite gas-sensitive materials, its electrochemical gas-sensitive performance can be effectively adjusted, and its response speed, selectivity and working conditions can be improved.

[0003] In recent years, with the in-depth advancement of research on clean and low-carbon energy, various new energy storage batteries have emerged. Among them, lithium batteries have become one of the mainstream energy storage devices in the market because they can work at higher voltages and have advantages such as high specific energy and long cycle life. However, during the use of batteries, the battery cells are usually arranged closely in a closed shell. When the battery module is operating in a complex and changeable environment, the heat of the battery module is not easy to transfer to the outside world, resulting in a large temperature difference between the cells. These situations will not only accelerate the degradation of the battery module, but also cause the battery module to burn or even explode in severe cases. Therefore, based on the safety, reliability and stability of the battery module, it is particularly important to select a suitable cooling method and design a corresponding cooling structure to effectively control the temperature of each cell inside the battery. Liquid cooling technology has been widely used in electrochemical energy storage systems, but the current research on the detection scheme for whether the liquid cooling component is leaking is very limited. The currently commonly used tin oxide-based gas sensors have poor responsiveness in ethanol detection applications and are insufficient in ethanol detection applications, making it difficult to detect leakage in ethylene glycol-based cooling systems. Summary of the invention

[0004] The purpose of the present invention is to overcome the technical problems in the prior art such as the poor responsiveness of tin oxide gas-sensitive materials in ethanol detection applications and the difficulty in detecting leakage of cooling medium in electrochemical energy storage liquid cooling systems, and to provide a composite gas-sensitive material and a preparation method and application thereof. The composite gas-sensitive material prepared by the method has high sensitivity to ethanol, and the composite gas-sensitive material is used to detect ethylene glycol-based coolant mixed with ethanol, and has the advantages of fast response, safety and stability, and can be widely used in leakage detection technology of electrochemical energy storage liquid cooling systems.

[0005] In order to achieve the above object, the present invention provides a method for preparing a composite gas-sensitive material, which comprises the following steps:

[0006] (1) in the presence of an organic alcohol solvent, a tin salt, an indium salt and a carbon source are mixed and reacted, and the product obtained after the reaction is cooled, washed and dried to obtain a tin-indium-based organic metal framework precursor;

[0007] (2) heating the tin-indium-based organic metal framework precursor to react.

[0008] Preferably, in step (1), the mass ratio of the tin salt, the indium salt and the carbon source is (1-8):1:(2-30), preferably (3-4):1:(10-15).

[0009] Preferably, in step (1), the mass volume ratio of the tin salt to the organic alcohol solvent is 250-350 mg:50 mL.

[0010] Preferably, in step (1), the reaction conditions include: temperature of 150-200°C, preferably 160-190°C; time of 20-30h, preferably 22-26h.

[0011] Preferably, the tin salt is tin chloride.

[0012] Preferably, the indium salt is indium nitrate.

[0013] Preferably, the carbon source is trimesic acid.

[0014] Preferably, in step (2), the heating reaction process includes: heating the tin-indium-based organic metal framework precursor to 500-1000°C at a heating rate of 1-10°C / min, and reacting at a constant temperature for 2-8 hours; further preferably, heating the tin-indium-based organic metal framework precursor to 600-900°C at a heating rate of 2-5°C / min, and reacting at a constant temperature for 3-5 hours.

[0015] A second aspect of the present invention provides a composite gas-sensitive material, which is prepared by the method described above.

[0016] The third aspect of the present invention provides the use of the composite gas-sensitive material in detecting ethanol.

[0017] A fourth aspect of the present invention provides a method for detecting leakage of an electrochemical energy storage liquid cooling system, the method comprising: adding ethanol to an ethylene glycol-based coolant, using the composite gas-sensitive material described above as a gas-sensitive material, and indirectly determining whether there is a coolant leakage by detecting the leakage of ethanol.

[0018] According to the preparation method of the composite gas-sensitive material of the present invention, by introducing indium element into the tin-based metal organic framework, using the tin-indium-based metal organic framework with a microsphere structure as a precursor, a composite gas-sensitive material having a microsphere structure and containing SnO 2 / In 2 O 3 A composite gas-sensitive material of / C is provided. The composite gas-sensitive material has high sensitivity to ethanol. The composite gas-sensitive material is used to detect ethylene glycol-based coolant mixed with ethanol. The composite gas-sensitive material has the advantages of fast response, safety and stability, and can be widely used in leakage detection technology of electrochemical energy storage liquid cooling system. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of the tin-indium-based organic metal framework precursor in Example 1 of the present invention;

[0020] Figure 2 is a scanning electron microscope image of the composite gas-sensitive material L1 in Example 1 of the present invention;

[0021] Figure 3 is an X-ray diffraction pattern of the tin-indium-based organic metal framework precursor in Example 1 of the present invention;

[0022] Figure 4 is the X-ray diffraction pattern of the composite gas-sensitive material L1 in Example 1 of the present invention;

[0023] Figure 5 is a transmission electron microscope image of the composite gas-sensitive material L1 in Example 1 of the present invention;

[0024] Figure 6 Element distribution diagram of the composite gas-sensitive material L1 in Example 1 of the present invention;

[0025] Figure 7 This is the energy spectrum test diagram of the composite gas-sensitive material L1 in Example 1 of the present invention;

[0026] Figure 8 is an X-ray photoelectron spectrum of the composite gas-sensitive material L1 in Example 1 of the present invention;

[0027] Fig. 9 The gas-sensing performance test results of the composite gas-sensing material L1 in Example 1 of the present invention;

[0028] Fig.10 The gas-sensitive stability test results of the composite gas-sensitive material L1 in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] The preparation method of the composite gas-sensitive material of the present invention comprises the following steps:

[0032] (1) in the presence of an organic alcohol solvent, a tin salt, an indium salt and a carbon source are mixed and reacted, and the product obtained after the reaction is cooled, washed and dried to obtain a tin-indium-based organic metal framework precursor;

[0033] (2) heating the tin-indium-based organic metal framework precursor to react.

[0034] The preparation method is used to introduce indium elements into tin-based metal-organic frameworks, and the preparation method is optimized by adjusting the doping amount of indium elements. The tin-indium-based metal-organic framework with a microsphere structure is used as a precursor material, and the microstructure of the material can be effectively regulated. The stable microsphere structure can effectively alleviate its structural changes during the recycling process and improve its stability and repeatability.

[0035] In the method of the present invention, in step (1), the mass ratio of the tin salt, the indium salt and the carbon source can be (1-8):1:(2-30), preferably (2-6):1:(4-28), further preferably (3-4):1:(10-15), and most preferably 3.5:1:12.5. In the present invention, tin, indium and carbon are used as three components to prepare the composite gas-sensitive material. The synergistic and complementary effects between the different components can significantly improve its gas-sensitive performance, improve its response speed, detection limit, selectivity and stability. Among them, the doping of a small amount of indium element can effectively improve the electrochemical activity of the composite gas-sensitive material and increase the active sites. After the carbon material is introduced, its conductivity and activity can be further improved.

[0036] In the method of the present invention, in step (1), the mass volume ratio of the tin salt to the organic alcohol solvent can be 250-350 mg:50 mL, preferably 280-320 mg:50 mL. The organic alcohol solvent can be an organic alcohol solvent commonly used in the art, and in a specific embodiment, the organic alcohol solvent is preferably methanol.

[0037] In the method of the present invention, in step (1), the reaction conditions may include: temperature of 150-200° C., preferably 160-190° C.; time of 20-30 h, preferably 22-26 h.

[0038] In the method of the present invention, in step (1), the washing process may include: first washing with water for 2-5 times, and then washing with ethanol for 2-5 times. Preferably, the water is pure water, and the ethanol is anhydrous ethanol.

[0039] In the method of the present invention, the tin salt is preferably tin chloride.

[0040] In the method of the present invention, the indium salt is preferably indium nitrate.

[0041] In the method of the present invention, the carbon source is preferably trimesic acid.

[0042] In a more preferred embodiment, the tin salt is SnCl 2 ·2H 2 O, the indium salt is In(NO 3 ) 3 4.5H 2 O. Wherein, the SnCl 2 ·2H 2 O. The In(NO 3 ) 3 4.5H 2 O and H 3 The mass ratio of BTC is (1-6): (3-25): 1, the SnCl 2 ·2H 2 The mass volume ratio of O to the methanol is 280-320 mg:50 mL.

[0043] In the method of the present invention, in step (2), the heating reaction process may include: heating the tin-indium-based organic metal framework precursor to 500-1000°C at a heating rate of 1-10°C / min, and reacting at a constant temperature for 2-8 hours; preferably, heating the tin-indium-based organic metal framework precursor to 600-900°C at a heating rate of 2-5°C / min, and reacting at a constant temperature for 3-5 hours.

[0044] The present invention also provides a composite gas-sensitive material prepared by the above method. The composite gas-sensitive material has a microsphere structure, which can effectively alleviate its structural changes during the cyclic use process and improve its stability and repeatability. 2 、In 2 O 3 and C multiple components, and the gas sensing performance can be significantly improved by utilizing the synergistic and complementary effects among different components.

[0045] The present invention also provides an application of a composite gas-sensitive material in detecting ethanol. The composite gas-sensitive material provided by the present invention has high sensitivity to ethanol, and can be used to detect ethylene glycol-based coolants mixed with ethanol, and has the advantages of fast response, safety and stability, etc. In addition, the preparation method of the composite gas-sensitive material is scientific and reasonable, safe and easy, with simple equipment, low cost, high product controllability, and can be mass-produced, and has broad industrial application prospects.

[0046] The present invention also provides a method for detecting leakage of an electrochemical energy storage liquid cooling system, the method comprising: adding ethanol to an ethylene glycol-based coolant, using the composite gas-sensitive material described above as a gas-sensitive material, and indirectly determining whether there is a coolant leak by detecting the leakage of ethanol. The method has the advantages of rapid response, high sensitivity, and high degree of automation, and can significantly improve the safety of the liquid cooling system and the electrochemical energy storage system, and ensure their safe and stable operation.

[0047] The following examples further illustrate the composite gas-sensitive material and its preparation method and application of the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.

[0048] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.

[0049] Example 1

[0050] (1) 350 mg of SnCl 2 ·2H 2 O, 100 mg of In(NO 3 ) 3 4.5H 2 O and 1250 mg H 3 BTC was mixed with 60 mL of methanol and stirred for 30 min. The mixed solution was transferred to a stainless steel reactor and reacted at 180 ° C for 24 h. After the reaction, it was naturally cooled to room temperature. The sample was washed three times with ultrapure water and anhydrous ethanol respectively, and dried to obtain a tin-indium-based organic metal framework precursor.

[0051] (2) The tin-indium-based organic metal framework precursor is placed in a muffle furnace, the heating rate is adjusted to 3° C. / min, and the reaction is carried out at 800° C. for 4 h to obtain a composite gas-sensitive material L1.

[0052] Figure 1This is a scanning electron microscope image (SEM) of the tin-indium-based organic metal framework precursor prepared in step (1). As can be seen from the figure, the material has a stable microsphere structure, a smooth surface, and no other impurities are generated.

[0053] Figure 2 This is the SEM image of the composite gas-sensitive material L1 in Example 1. It can be seen from the figure that the composite material maintains the microsphere structure of the precursor, and its stable structural characteristics are more conducive to improving its gas-sensitive cyclic stability.

[0054] Figure 3 This is the X-ray diffraction pattern (XRD) of the tin-indium-based organic metal framework precursor in Example 1. It can be seen from the figure that the spectrum is completely consistent with the characteristic peaks of the metal organic framework material, indicating that the doping of indium element does not affect the crystal structure of the material; and no other impurity peaks are seen in the spectrum, and the diffraction peaks are sharp, indicating that the purity and crystallinity of the precursor are very high, and no other impurities are generated.

[0055] Figure 4 The XRD diagram of the composite gas-sensitive material L1 in Example 1 shows that its characteristic peak is similar to that of SnO 2 (PDF#41-1445) and In 2 O 3 (PDF#06-0416), indicating that the composite material contains two crystal structures.

[0056] Figure 5 This is the transmission electron microscope (TEM) image of the composite gas-sensitive material L1 in Example 1. It can be seen from the figure that the composite material is a solid microsphere structure with uniform size, which is consistent with the characterization results of the SEM image in Test Example 1.

[0057] Figure 6 : is the element distribution diagram of the composite gas-sensitive material L1 in Example 1. It can be seen from the figure that the composite material is composed of four elements: C, O, Sn, and In, and each element is evenly distributed, which proves the successful doping of C and In.

[0058] Figure 7 The energy spectrum test diagram (EDS) of the composite gas-sensitive material L1 in Example 1 shows that the composite material is composed of four elements: C, O, Sn, and In, which is consistent with the characterization result of the element distribution diagram in Test Example 4. Among them, the content of Sn is significantly higher than that of In, indicating that SnO 2 As the main component.

[0059] Figure 8X-ray photoelectron spectrum (XPS) of the composite gas-sensitive material L1 in Example 1. It can be seen from the figure that the composite material is composed of four elements: C, O, Sn, and In. The three characteristic peaks fitted from the C1s spectrum correspond to CC, CO, and C=O, respectively. The three characteristic peaks fitted from the O1s spectrum correspond to Sn-O, Sn-OC, and C=O, respectively. The characteristic peaks of the In3d spectrum correspond to In3d 3 / 2 and In3d 5 / 2 ; The characteristic peaks of the Sn3d spectrum correspond to Sn3d 3 / 2 and Sn3d 5 / 2 The above characterization data prove that the composite gas-sensitive material is composed of SnO 2 / In 2 O 3 / C was successfully synthesized.

[0060] The composite gas-sensitive material L1 in Example 1 of the present invention was tested for its gas-sensitive performance at a working temperature of 280° C., wherein the leakage of the ethylene glycol-based coolant was 1 mL, and the amount of anhydrous ethanol added was 0% to 1%. Fig. 9 It can be seen that when the addition amount of anhydrous ethanol reaches 0.1% and above, it has significantly excellent detection sensitivity. When the addition amount of anhydrous ethanol is 0.01% and above, the responsiveness changes suddenly. The results show that the composite gas-sensitive material has excellent sensitivity to the detection of ethanol doped in the coolant and can be used in leakage detection systems.

[0061] The composite gas-sensitive material L1 in Example 1 of the present invention was subjected to a stability gas-sensitive test at a working temperature of 280° C., wherein the leakage of the ethylene glycol-based coolant was 1 mL and the amount of anhydrous ethanol added was 0.05%. Fig.10 It can be seen that the response and baseline resistance of the composite gas-sensitive material remain basically constant, indicating that it has excellent stability in use and broad application prospects.

[0062] Example 2

[0063] (1) 300 mg of SnCl 2 ·2H 2 O, 50 mg In(NO 3 ) 3 4.5H 2 O and 1200 mg of H 3 BTC was mixed with 50 mL of methanol and stirred for 10 min. The mixed solution was transferred to a stainless steel reactor and reacted at 160 ° C for 22 h. After the reaction, it was naturally cooled to room temperature. The sample was washed three times with ultrapure water and anhydrous ethanol respectively, and dried to obtain a tin-indium-based organic metal framework precursor.

[0064] (2) The tin-indium-based organic metal framework precursor is placed in a muffle furnace, the heating rate is adjusted to 2° C. / min, and the reaction is carried out at 600° C. for 3 h to obtain a composite gas-sensitive material L2.

[0065] Example 3

[0066] (1) 400 mg of SnCl 2 ·2H 2 O, 200 mg of In(NO 3 ) 3 4.5H 2 O and 1300 mg of H 3 BTC was mixed with 70 mL of methanol and stirred for 50 min. The mixed solution was transferred to a stainless steel reactor and reacted at 190 ° C for 22 h. After the reaction, it was naturally cooled to room temperature. The sample was washed three times with ultrapure water and anhydrous ethanol respectively, and dried to obtain a tin-indium-based organic metal framework precursor.

[0067] (2) The tin-indium-based organic metal framework precursor is placed in a muffle furnace, the heating rate is adjusted to 5° C. / min, and the reaction is carried out at 700° C. for 5 hours to obtain a composite gas-sensitive material L3.

[0068] Example 4

[0069] (1) 400 mg of SnCl 2 ·2H 2 O, 300 mg of In(NO 3 ) 3 4.5H 2 O and 1400 mg of H 3 BTC was mixed with 65 mL of methanol and stirred for 60 min. The mixed solution was transferred to a stainless steel reactor and reacted at 180 °C for 24 h. After the reaction, it was naturally cooled to room temperature. The sample was washed three times with ultrapure water and anhydrous ethanol respectively, and dried to obtain a tin-indium-based organic metal framework precursor.

[0070] (2) The tin-indium-based organic metal framework precursor is placed in a muffle furnace, the heating rate is adjusted to 4° C. / min, and the reaction is carried out at 900° C. for 3 h to obtain a composite gas-sensitive material L4.

[0071] Example 5

[0072] (1) 350 mg of SnCl 2 ·2H 2 O, 350 mg In(NO 3 ) 3 4.5H 2 O and 1250 mg H 3BTC was mixed with 60 mL of methanol and stirred for 30 min. The mixed solution was transferred to a stainless steel reactor and reacted at 170 ° C for 26 h. After the reaction, it was naturally cooled to room temperature. The sample was washed three times with ultrapure water and anhydrous ethanol respectively, and dried to obtain a tin-indium-based organic metal framework precursor.

[0073] (2) The tin-indium-based organic metal framework precursor is placed in a muffle furnace, the heating rate is adjusted to 5° C. / min, and the reaction is carried out at 800° C. for 4 hours to obtain a composite gas-sensitive material L5.

[0074] Comparative Example 1

[0075] The composite gas-sensitive material was prepared according to the method of Example 1, except that In(NO 3 ) 3 4.5H 2 O, and obtain the composite gas-sensitive material M1.

[0076] Test Example 1

[0077] The composite gas-sensitive materials prepared in Examples 1-5 and Comparative Example 1 were respectively tested for gas-sensitive performance, and the test method included: adding 0.01 mL of anhydrous ethanol to 1 mL of ethylene glycol-based coolant, using the composite gas-sensitive material as a gas-sensitive material to detect ethanol, and characterizing the sensitivity to ethanol by the response value. The test results are shown in Table 1. Among them, the higher the response value, the higher the detection sensitivity of the gas-sensitive material to ethanol, and vice versa.

[0078] Table 1

[0079]

[0080] It can be seen from the data in Table 1 that in the detection of ethanol with the same content, the response value of the composite gas-sensitive material in the present invention is much greater than that of the composite gas-sensitive material in the comparative example, especially under preferred conditions. Therefore, the composite gas-sensitive material obtained by the preparation method of the composite gas-sensitive material of the present invention has significantly higher sensitivity to ethanol. The composite gas-sensitive material is used to detect ethylene glycol-based coolant mixed with ethanol, and has the advantages of fast response, safety and stability, and is more suitable for leakage detection technology of electrochemical energy storage liquid cooling system.

[0081] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite gas-sensitive material, characterized in that: The method comprises the following steps: (1) in the presence of an organic alcohol solvent, a tin salt, an indium salt and a carbon source are mixed and reacted, and the product obtained after the reaction is cooled, washed and dried to obtain a tin-indium-based organic metal framework precursor; (2) heating the tin-indium-based organic metal framework precursor to react.

2. The method according to claim 1, characterized in that In step (1), the mass ratio of the tin salt, the indium salt and the carbon source is (1-8):1:(2-30), preferably (3-4):1:(10-15).

3. The method according to claim 1 or 2, characterized in that: In step (1), the mass volume ratio of the tin salt to the organic alcohol solvent is 250-350 mg:50 mL.

4. The method according to any one of claims 1 to 3, characterized in that: In step (1), the reaction conditions include: temperature of 150-200° C., preferably 160-190° C.; time of 20-30 h, preferably 22-26 h.

5. The method according to any one of claims 1 to 3, characterized in that: The tin salt is tin chloride.

6. The method according to any one of claims 1 to 3, characterized in that: The indium salt is indium nitrate.

7. The method according to any one of claims 1 to 3, characterized in that: The carbon source is trimesic acid.

8. The method according to claim 1, characterized in that In step (2), the heating reaction process includes: heating the tin-indium-based organic metal framework precursor to 500-1000° C. at a heating rate of 1-10° C. / min, and reacting at a constant temperature for 2-8 hours; Preferably, the tin-indium-based organic metal framework precursor is heated to 600-900° C. at a heating rate of 2-5° C. / min, and reacted at a constant temperature for 3-5 hours.

9. A composite gas-sensitive material prepared by the method according to any one of claims 1 to 8.

10. Use of the composite gas-sensitive material according to claim 9 in detecting ethanol.

11. A method for detecting leakage of an electrochemical energy storage liquid cooling system, characterized in that: The method comprises: adding ethanol to an ethylene glycol-based coolant, using the composite gas-sensitive material according to claim 9 as a gas-sensitive material, and indirectly judging whether there is a coolant leak by detecting the leakage of ethanol.